PENGARUH DISIPLIN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DINAS LINGKUNGAN HIDUP DAERAH PROVINSI SULAWESI TENGAH - Indrajaya, Indrajaya (Katalogis, 2018)
The Department of Environment of Central Sulawesi Province together with the local government formulates policies in the field of environmental protection and management. The study aims to determine and analyze simultaneous and partial influence of discpline and organizational climate on officials’ performance in The Department of Environment, Central Sulawesi Province. Sample of 49 officials selected with census method. Method of analysis is multiple linear regressions with quantitative approach. The result shows that work discipline and organizational climate simultaneously and partially have significant influence on officials’ performance in The Department of Environment, Centra Sulawesi Province.